Robotically performed diagnostic coronary angiography. Issue 2 (27th May 2022) - Joseph, Timothy; VanOosterhout, Stacie; Negash, Araya; VanLoo, Lisa; Redmond, Meaghan; Parker, Jessica L.; McNamara, David A.; Madder, Ryan D.
Abstract: Objective: This study was performed to investigate the efficacy and safety of robotic diagnostic coronary angiography. Background: Robotic percutaneous coronary intervention is associated with marked reductions in physician radiation exposure. Development of robotic diagnostic coronary angiography might similarly impact occupational safety. Methods: Stable patients referred for coronary angiography were prospectively enrolled. After obtaining vascular access, diagnostic catheters were manually advanced over a wire to the ascending aorta. All subsequent catheter movements were performed robotically. The primary endpoint was procedural success, defined as robotic completion of coronary angiography without conversion to a manual procedure and the absence of procedural major adverse cardiovascular events (MACE—cardiac death, cardiac arrest, or stroke) and major angiographic complications (coronary/aortic dissection or embolization). The primary hypothesis was that the observed rate of the primary endpoint, evaluated at the completion of coronary angiography, would meet a pre‐specified performance goal of 74.5%. Results: Among 46 consecutive patients (age 67 ± 12 years; 69.6% male), diagnostic coronary angiography was completed robotically in all cases without the need for manual conversion and without any MACE or major angiographic complications. Thus, procedural success was 100%, which was significantly higher than the pre‐specified performance goal ( p  < 0.001). Robotic coronary angiography was completed using 2 [2, 3] catheters per case with a median procedural time of 15 [11, 20] minutes. Conclusions: Robotic diagnostic coronary angiography was performed with 100% procedural success and no observed complications. These results support the performance of future studies to further explore robotic coronary angiography.